The Influence of General Exceptions on the Interpretation of National Treatment in International Investment Law - Louis-Marie, Chauvel (2017)
Recent International Investment Agreements have incorporated General Exceptions similar to GATT Article XX in order to balance the respect of National Treatment and protection of States’ right to regulate. The purpose of this piece is to determine if these exceptions are a suitable choice in order to achieve this objective or if another option would be preferable. We first established that General Exceptions are operative exceptions and not interpretative statements. This allowed to assess their effect on the interpretation of national treatment and we managed to prove their potentially detrimental effect on the right to regulate. Then, we searched for other means to interpret National Treatment compatible with general exceptions but none appears to be really effective in achieving the purpose to balance protection of investments and State’s right to regulate. As a consequence, a final study for other treaty wording achieving the stated objective allows to conclude that the most suitable choice would be to codify selected arbitral award allowing to take into account public policy objectives to determine if two investors are in same circumstances, therefore securing the contemplated balance.